Epigenetic mechanisms in heart development and disease. Issue 7 (July 2015) - Martinez, Shannalee R.; Gay, Maresha S.; Zhang, Lubo
Highlights Epigenetic mechanisms influence gene expression at key cardiac developmental stages and during major cellular events. Epigenetic mechanisms can directly contribute to the development of cardiovascular diseases. Epigenetic mechanisms represent novel and promising targets for therapeutic development in the treatment of cardiovascular diseases.